Bioremediation of lead-contaminated paddy field by using ramie, agrobacterium and organic matter. (December 2019) - Rosariastuti, R; Kartika, K; Aryani, W; Supriyadi,
Abstract: Lead (Pb) contamination is one of environmental issue because of its great influence on human health and ecological system. Paddy fields in Karanganyar, Indonesia are indicated to be contaminated by Pb, due to many local industries that dispose their effluents in local water ways. This research aimed to investigate the influence of combined application of Ramie ( Boehmeria nivea )-Chelator-Inorganic Fertilizers on the change of Pb level in soil. The experiment was arranged in experimental factorial design using Randomized Complete Block Design as the based design, consist of three factorsand three replications. First factor was Inorganic fertilizer consist of without inorganic fertilizers (p0 ) and with inorganic fertilizers (p1 ); second factor was chelator (B) consist of without chelator (b0 ), chelator of Agrobacterium sp. I3 (b1 ) and chelator of compost (b2 ); the last factor was Ramie (T) consist of without ramie (t0 ) and with ramie application (t1 ). The main parameter observed in this research was effectivity of phytoremediation and Pb levels in soil and in plant shoot and root. Data was analyzed by statistical analysis using ANOVA continued by DMRT, T-Test and Correlation Test. The results showed that interaction between inorganic fertilizers, chelator and ramie clearly enhanced total bacterial colonies. Ramie was able to decreased Pb level in soils up to 29.51%. Agrobacterium sp. I3 increased effectivity of Ramie in decreasing Pb level in soil. The phytoremediation effectivity increased up to 41.82% by increasing roots Pb uptake (9.78 μg) and shoots Pb uptake (25.97 μg). Compost decreased roots Pb uptake (1.74 μg) and shoots Pb uptake (14.85 μg).